MICRO-MORPHOLOGY STUDY OF POLLEN GRAINS AND CYPSELA OF SEVEN SELECTED SPECIES, BELONG TO ASTERACEAE FAMILY IN AL-JADRIYA CAMPUS - & Aliwy, Sadeq (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Seven plants species that belong to Asteraceae (Compositae) family have been investigated micro-morphology with the help of scanning electron microscopy (SEM) observations. Plants were collected from University of Baghdad campus during January to May in 2017-2018 and the species are: Calendula persica C. M. May, Carduus pycnocephalus L., Erigeron canadensis L., Lactuca serriola L., Silybum marianum (L.) Garth, Sonchus oleraceus L., Urospermum picroides (L.) Schmidt. The aim of this study was to describing the external morphology of seeds as well as a detailed study of pollen grains morphology. Special emphasis is given to the size, shape, polar and equatorial length, spines length, length and width of ora and colpi, tectum sclupturing, and the ornamentations on pollen surface, Sonchus oleraceus and Lactuca serriola pollen grains have a special exin sculpture, which is lophate and the other species used in this study is non-lophate, and all the pollen grains of the species used in this study are tri-zono- colporate, Calendula persica is only species that it is exin sculpture is echinate with spines length (3.8-4.3 um), and the exin sculpture of the other species is spinulose. Also special importance is given to the size, shape, pappus, beak length, primary and secondary sculpturing, carpopodium, as well as the surface of the seed (Cypsela), Seeds (cypsela) of the species used in this study were significantly different in morphology, The shapes of the 7 species were differed in each species and it showed 7 different shapes: narrowly-oblong, oblong, long-oblong, board-oblong, widely curved-oblong, narrowly-ellipitic, and narrowly-obovated.